2012
DOI: 10.4049/jimmunol.1102276
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and Galectin-1 Modulate HIV-1 Infection of Human Monocyte-Derived Macrophages

Abstract: Morphine is a widely abused, addictive drug that modulates immune function. Macrophages are a primary reservoir of HIV-1; therefore, they play a role in the development of this disease, as well as impact the overall course of disease progression. Galectin-1 is a member of a family of β-galactoside–binding lectins that are soluble adhesion molecules and that mediate direct cell–pathogen interactions during HIV-1 viral adhesion. Because the drug abuse epidemic and the HIV-1 epidemic are closely interrelated, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Previously, we have shown that addictive drugs such as opiates like morphine and Meth increased the expression of Galectin-1 in human monocytes-derived macrophages (MDM) and exogenous Galectin-1 and morphine potentiated HIV-1 infection of MDM (Reynolds JL, et al 2012 a ; Reynolds JL, et al 2012 b ). These studies demonstrated that Galectin-1 was an important mediator involved in immune-mediated responses observed in HIV-1 infected drug abusing subjects and that Galectin-1 could be included as a therapeutic target in combination therapy for HIV-1 infected drug abusers.…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that addictive drugs such as opiates like morphine and Meth increased the expression of Galectin-1 in human monocytes-derived macrophages (MDM) and exogenous Galectin-1 and morphine potentiated HIV-1 infection of MDM (Reynolds JL, et al 2012 a ; Reynolds JL, et al 2012 b ). These studies demonstrated that Galectin-1 was an important mediator involved in immune-mediated responses observed in HIV-1 infected drug abusing subjects and that Galectin-1 could be included as a therapeutic target in combination therapy for HIV-1 infected drug abusers.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Further, we have shown that the Galectin expression levels may be modulated by viral infections and inflammatory agents such as drugs of abuse but whether they directly or indirectly alter BBB permeability is not known. (Reynolds JL, et al 2012 a ; Reynolds JL, et al 2012 b ). …”
Section: 0 Introductionmentioning
confidence: 99%
“…These effects were mediated, in part, by increased surface CCR5, supporting the concept that morphine enhances HIV entry into macrophages by regulating the surface expression of its co-receptors [92]. Another proposed mechanism is the regulation of adhesion molecules that mediate pathogen-host interactions [90]. Galectin -1 is a soluble adhesion molecule secreted by many cell types including macrophages.…”
Section: Regulation Of Monocyte Migration and Macrophage Inflammatmentioning
confidence: 91%
“…It has been shown that morphine enhances HIV infection of and replication in macrophages and other CNS resident cells (Fig. 1C) [8890]. Many factors have been proposed to contribute to this process.…”
Section: Regulation Of Monocyte Migration and Macrophage Inflammatmentioning
confidence: 99%
See 1 more Smart Citation